The Communicative Paradox: Notebooks and Workbooks of the Russian Avant-garde “Big Three” - Lyubov V. Khachaturian (Studia Litterarum)
The article provides a comparative analysis of the workbooks and notebooks of Vladimir Mayakovsky, Velimir Khlebnikov, and Alexey Kruchenykh. The analysis of draft recordings, most of which are hitherto unpublished, demonstrates a commonality of techniques for creating a literary text far beyond the boundaries of the documented co-authorship of 1912–1914. The study explains this phenomenon by returning to the classical model of the communicative structure of the text. The article demonstrates correlations between the theoretical positions of the Tartu-Moscow semiotic school and various sources. It clarifies the operating mechanism of the structural pair “I — He” vs “I — Me.” The research pays special attention to the autocommunication of the literary text and reconstructs its action through Alexey Kruchenykh’s work notes from 1927 to 1930. The article also focuses on the “technique of creative splitting” developed by Kruchenykh after the death of Khlebnikov and Mayakovsky (Mikhail Lotman). The established patterns allow us to trace gradually the process of creating an abstruse language, in which two root morphemes form a new lexeme (Maxim Shapir): the original version is restored, and then the synonymic series and the final integrated text are fixed.